THE ROLE OF AIR HUMIDITY IN THE LIFE OF LIVING ORGANISMS - Ubaydullaeva Vazira Pachchahanovna; Azamov Murodjon Umid ogli; Tokhirov Samandar Ulugbek ogli; Inomjanov Yosinjon Shukhrat ogli (Modern American Journals, 2025)
Air humidity is one of the most important ecological and biophysical factors, determining the intensity of heat exchange, evaporation, respiration, and water balance in living organisms. This article examines the physical parameters of humidity and their effects on the physiological processes of humans, animals, and plants. The biophysical mechanisms of humidity influence are highlighted, including the role of water vapor partial pressure, saturation deficit, and the equilibrium between evaporation and heat dissipation. The main consequences of both low and high humidity levels are presented, as well as their significance for the vitality and functioning of living organisms.
Keywords: Air humidity; biophysics; partial pressure; evaporation; heat exchange; transpiration; dehydration; ecology; water balance; living organisms.